Mythological Allusion in the Late Verse of Egill Skallagrímsson - Sayers, William (Scandinavian-Canadian Studies / Études scandinaves au Canada, 2025)
The essay examines Egill Skallagrímsson’s renunciation of his veneration of Óðinn, the god of war and poetry, in the poem Sonatorrek. References to this patron and to the whole corpus of early Scandinavian mythology almost entirely disappear from the verse Egill composed over the last decades of his life. The events and emotional state that prompted this decision and the procedure by which it was effected is examined in detail.